Effects of size of ingestively masticated fragments of plant tissues on kinetics of digestion of NDF - Ellis, WC; Mahlooji, M; Lascano Aguilar, Carlos Eduardo; Matis, JH (2005)
Ingestively masticated fragments were collected and sized via sieving. Different sizes of esophageal masticate and ruminal digesta fragments, and ground fragments of larger masticated pieces were incubated in vitro, and undigested NDF remaining at intervals of up to 168 h of incubation was determined. The ruminal age-dependent time delay (?) for onset of digestion of NDF was positively correlated (P < 0.004) with the mean sieve aperture estimated to retain 50% of the fragments between successive sieve apertures (MRA). Degradation rate of potentially degradable NDF (PDF) and level of indigestible NDF were not related (P > 0.10) to MRA of masticated and ground fragments. Estimates of ? were positively related to MRA, with slopes of bermudagrass < corn silage < ruminal fragments of corn silage. It was concluded that fragment size-, and consequently, ruminal age-dependent onset of PDF degradation of a mixture of different fragment sizes results in an age-dependent rate of degradation of the more rapidly degrading of two subentities of PDF. Models are proposed that assume a ? before onset of simultaneous degradation of PDF from two pools characterized as having gamma-modeled age-dependency and age-constant rates. The ruminal age-dependent pool seems to be associated with the faster-degrading pool, and its rate parameter increases with range in MRA in the population of fragments. Conceptually, the ruminal age-dependent rate parameter for PDF degradation seems to represent a composite of several effects: 1) effects of the size-dependent ?; 2) range in MRA of the population of ingestively masticated fragments; and 3) subentities of PDF that degrade via more rapid age-dependent rates compared with subentities of PDF that degrade via age-constant rates. The estimated fractional rates of ruminative comminution of ingestively masticated fragments (0.060 to 0.075/h) were of a magnitude similar to the mean fractional rates of PDF digestion (0.030 to 0.085/h), which implies that ruminative comminution may be first-limiting to fractional rate of PDF digestion. The in vivo roles of ingestive and ruminative mastication of fragments on PDF degradation must be considered in any kinetic system for estimating PDF digestion in the rumen. These results and others in the literature suggest that the rate of surface area exposure rather than intrinsic chemical attributes of PDF may be first-limiting to degradation rate of PDF in vivo.